Proceedings of the 2017 ACM Conference on Computer Supported Cooperative Work and Social Computing 2017
DOI: 10.1145/2998181.2998228
|View full text |Cite
|
Sign up to set email alerts
|

Challenges on the Journey to Co-Watching YouTube

Abstract: In order to better understand social aspects of the short-form video watching experience, we investigated the journey to cowatching, from searching and discovering content, to choosing and experiencing videos with others. After identifying, through a large-scale survey, some of the most typical situations that bring people to YouTube, we deployed a one weeklong diary study with 12 participants in which they performed a set of frequent video tasks at their leisure, half by themselves, and half with someone else… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(29 reference statements)
3
12
0
Order By: Relevance
“…Participants were rarely alone (10.5%); mutual connection motivations were mostly addressed in a co-watching experience with a group (43.9%) or a pair (42.1%). In agreement with related work [16], we observed that negotiation on a video to watch can take significant time and be detrimental to the experience, e.g. "Took too long and we lost interest".…”
Section: Mutually Connectsupporting
confidence: 92%
See 4 more Smart Citations
“…Participants were rarely alone (10.5%); mutual connection motivations were mostly addressed in a co-watching experience with a group (43.9%) or a pair (42.1%). In agreement with related work [16], we observed that negotiation on a video to watch can take significant time and be detrimental to the experience, e.g. "Took too long and we lost interest".…”
Section: Mutually Connectsupporting
confidence: 92%
“…They could also voluntarily fill the survey at any time to report a video watch without waiting for a probe. By using this method, we collected information about participants' video watches at close proximity to when the experience happened (usually not more than a few hours after the event), thus making it more likely to capture an infrequent motivation in comparison to using single surveys [13,3,7,16]. Figure 1 shows examples of the ESM notification and probing survey.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations